2014
DOI: 10.1177/0300060514525351
|View full text |Cite
|
Sign up to set email alerts
|

The analgesic efficacy and safety of nefopam in patient-controlled analgesia after cardiac surgery: A randomized, double-blind, prospective study

Abstract: Objective: The efficacy and side-effects of nefopam were prospectively compared with those of fentanyl for patient-controlled analgesia (PCA) following cardiac surgery. Methods: Patients scheduled to undergo cardiac surgery were randomly assigned between three PCA groups (nefopam, fentanyl or nefopam þ fentanyl). Pain was assessed at rest and during movement at 12, 24, 36, 48 and 72 h after surgery using a visual analogue scale (VAS). Total infused PCA volume, number of rescue drug injections, duration of intu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 29 publications
3
40
0
Order By: Relevance
“…The study was performed according to the guidelines of the Declaration of Helsinki [4] and was registered with the Chinese Clinical Trials Registry (CCTR no. 003241).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study was performed according to the guidelines of the Declaration of Helsinki [4] and was registered with the Chinese Clinical Trials Registry (CCTR no. 003241).…”
Section: Methodsmentioning
confidence: 99%
“…The use of a combination of analgesics from different pharmacological drug classes to manage post-operative pain should improve the safety and efficacy of pain therapy due to their different mechanisms of action and by limiting the severity of adverse events of the individual drugs, since opioids alone sometimes provide insufficient post-operative analgesia. Understandably, a demand exists for the clinical investigation of drugs with special reference to adverse events, for analgesic use as part of combination therapy during the post-operative period [4].…”
Section: Introductionmentioning
confidence: 99%
“…Even though tachycardia and profuse sweating occurred more frequently, many studies reported that these adverse events associated with nefopam were not observed or were minor. In addition, nefopam was recently reported to cause frequent injection pain [24]. Kim et al [24] showed that the incidence of injection pain was lower in patients infused with 30 mg nefopam at 60 ml/h (over 20 minutes), compared with that at a rate greater than 120 ml/h (below 10 minutes).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, nefopam was recently reported to cause frequent injection pain [24]. Kim et al [24] showed that the incidence of injection pain was lower in patients infused with 30 mg nefopam at 60 ml/h (over 20 minutes), compared with that at a rate greater than 120 ml/h (below 10 minutes). Kim and Abdi [11] also suggested that intravenous nefopam should be slowly infused in single doses of 20 mg over 15 to 20 minutes to minimize adverse effects during treatment of neuropathic pain.…”
Section: Discussionmentioning
confidence: 99%
“…(17) The analgesic mechanism of nefopam is unique, and, to date, fewer adverse effects, such as sedation (25%), sweating (23.9%), tachycardia (12%), and nausea (10.9%), have been reported. (18) Nefopam may be a reasonable alternative for analgesia in trauma patients in acute care settings such as the ED.…”
Section: Discussionmentioning
confidence: 99%